2011
DOI: 10.5902/217976922513
|View full text |Cite
|
Sign up to set email alerts
|

A metodologia de Callista Roy aplicada em clientes submetidos à intervenção hemodinâmica

Abstract: RESUMO: Trata-se de uma pesquisa qualitativa, do tipo exploratório descritiva, que identificou o perfil de saúde dos clientes em tratamento hemodinâmico e desenvolveu o Processo de Enfermagem (PE), fundamentado em Callista Roy. Realizou-se com 52 clientes, no Centro de Hemodinâmica de um hospital privado, de fevereiro a maio de 2010. Utilizouse um questionário semiestruturado para coleta de dados. A maioria tinha mais de 60 anos, aposentados, casados, moradores de Chapecó, com ensino fundamental. Os fatores de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
1
2
0
1
Order By: Relevance
“…Another investigation evaluated the pain of patients who underwent haemodynamic procedures and found that, although the surgical wound was small, these surgeries caused acute pain, discomfort, and changes in blood pressure associated with the harmful factors and the introduction of catheters. These results agree with the analysed study (15) . Given the significant number of patients who reported pain in the immediate postoperative period, it must be the focus of nursing staff and multi-professional teams.…”
Section: Discussionsupporting
confidence: 93%
“…Another investigation evaluated the pain of patients who underwent haemodynamic procedures and found that, although the surgical wound was small, these surgeries caused acute pain, discomfort, and changes in blood pressure associated with the harmful factors and the introduction of catheters. These results agree with the analysed study (15) . Given the significant number of patients who reported pain in the immediate postoperative period, it must be the focus of nursing staff and multi-professional teams.…”
Section: Discussionsupporting
confidence: 93%
“…Some Brazilian studies (12)(13)(14)(15) used this model. However, none of them concern patients on dialysis.…”
Section: Discussionmentioning
confidence: 99%
“…The fourth is the setting of goals and the fifth is the planning of the interventions. [7][8][9]11 Roy's Theory allows us to recognize that people, through stimuli, can trigger positive or negative responses in different situations. By enabling nurses to implement care actions that favor adaptive responses, thus contributing to adherence to the treatment and better quality of life of patients with coronary artery disease who will undergo invasive hemodynamic procedures, since they must undergo a process of adaptation to the new health condition and disease.…”
Section: Introductionmentioning
confidence: 99%